World Health Organization (WHO) guideline on the complementary feeding of infants and young children aged 6-23 months 2023: A multisociety response (Journal of pediatric gastroenterology and nutrition, 2024)
The recent World Health Organization (WHO) guideline aims to provide evidence-based recommendations on complementary feeding (CF) of healthy term infants and young children 6-23 months living in low-, middle-, and high-income countries, including both breastfed and non-breastfed children. Like WHO, our organizations aim to promote optimal infant and young child nutrition and health, with a focus on promoting breastfeeding as well as appropriate and timely CF. In this paper, we share our concerns about aspects of the guideline, some of which may have the potential to cause unintended harm in infants and young children and suggest alternative or modified proposals.